Strategi Akomodasi Komunikasi Bisnis Jasa Pada Pelanggan Multikultural dalam Proses Membanguin Kenyamanan Pelanggan: Studi Kasus Barbershop Terthecut Yogyakarta - Yudhiarta, I Made Boby; Prasetyawibowo, Aaron Reghanada; Irwansyah, Irwansyah (Universitas 17 Agustus 1945 Surabaya, 2026)
This study aims to analyze communication accommodation strategies employed by barbers in fostering customer comfort within a multicultural service context. While Communication Accommodation Theory (CAT) has been widely applied in formal communication settings, its application in interpersonal service interactions involving direct contact and cultural diversity remains underexplored. This study adopts a qualitative approach, utilizing in-depth interviews, literature review, and documentation. Informants were selected through purposive sampling, involving barbers from three branches of Terthecut Barbershop Yogyakarta (Demangan, Palagan, and Condong Catur) as well as customers from outside the region. The findings reveal that barbers employ accommodation strategies situationally through convergence, divergence, and particularly maintenance, based on a process of quick screening of customers’ characteristics, communication preferences, and emotional states. Maintenance strategies, such as the consistent use of Indonesian as a standard greeting and standardized service gestures, play a crucial role in maintaining interactional stability and professionalism in multicultural encounters. These findings suggest that communication accommodation in service settings operates as a dynamic and adaptive process, extending beyond identity alignment toward the management of interpersonal dynamics. This study contributes to the extension of CAT within service contexts and highlights the role of communication in shaping customers’ affective comfort. Keywords: Communication accommodation theory, Multicultural customer, Customer comfort, Business services.